2003
DOI: 10.1051/lait:2003002
|View full text |Cite
|
Sign up to set email alerts
|

Prepurification of ?-lactalbumin with ultrafiltration ceramic membranes from acid casein whey: study of operating conditions

Abstract: -A promising way to produce purified a-lactalbumin (a-LA) is to perform a two-step cascade. The first step of pre-purifying presented herein, consists of ultrafiltration (UF) fractionation of acid casein whey, aiming at increasing the purity of a-LA in the filtrate by total retention of bovine serum albumin and immunoglobulins with only a limited transmission of b-lactoglobulin. The outcome of the present work is a guideline which includes the proper selection of ceramic UF membrane molecular mass cut-off (MMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…The feeds used in the present work were prepared according to the principles of α-LA prepurification reported by Muller et al [15]. Nonetheless, the actual operating conditions were adapted to the whey protein fractions specially selected for the present work.…”
Section: Feedsmentioning
confidence: 99%
See 2 more Smart Citations
“…The feeds used in the present work were prepared according to the principles of α-LA prepurification reported by Muller et al [15]. Nonetheless, the actual operating conditions were adapted to the whey protein fractions specially selected for the present work.…”
Section: Feedsmentioning
confidence: 99%
“…Detailed flow-sheets for the industrial manufacture of liquids PS 75 and PS 90 have been reported by Muller [13] and Gésan et al [9]. PS 90 ultrafiltrate and PS 90 microfiltrate were prepared as described by Muller et al [15] and were used as feeds for the ultrafiltration route (Fig. 1).…”
Section: Feedsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the test pH of 6, a-La proteins and the membrane are negatively charged and repulsion forces may explain the lower transmission. We can compare our data with those of Muller et al (2003) who used mineral membranes of 150 kDa. They reported a higher a-La transmission of 0.4, but at a lower permeate flux of about 50 L h À1 m À2 .…”
Section: Discussionmentioning
confidence: 89%
“…The next fractionation step is the separation and purification of major whey proteins such as a-La and b-Lg which present various applications for the food and pharmaceutical industries. a-La is used as food additive in infant formula (Muller, Chaufer, Merin, & Daufin, 2003) due to its high tryptophan content and nutritional value and has also medical applications due to its high cytotoxicity (Svensson, Hakansson, Mossberg, Linse, & Svanborg, 2000). b-Lg proteins have important emulsification and gelling properties (Cayot & Lorient, 1997;Dunlap & Coté, 2005).…”
Section: Introductionmentioning
confidence: 99%